PENDAFTARAN TANAH SECARA ELEKTRONIK PADA KANTOR PERTANAHAN KABUPATEN GARUT DITINJAU DARI ASPEK HUKUM ADMINSTRASI NEGARA - Manurung, Konrad (Berajah Journal, 2024)
Land registration is one way to obtain legal certainty by obtaining a land certificate. The electronic land registration program is being promoted, this is done to speed up service, completion time and affordable costs. The manual land registration process takes a long time, so the solution to speed up this service is an electronic land registration system. The implementation of land registration is based on simplicity, safety, affordability, up-to-date and open, so that provisions regarding land service procedures need to be adapted to developments in law, technology and community needs. The aim of this research is to determine the urgency of electronic land registration in Garut Regency, what is the legal force in electronic land registration. The theories used are the theory of legal protection by Satjipto Rahardjo and the Theory of Legal Certainty by Hans Kelsen. The method used is a qualitative approach with empirical normative legal research techniques and uses secondary data in the form of library books, tertiary materials in the form of the problems being discussed. Electronic land registration is carried out for the purposes of increasing Ease of Doing Business at the international level and to improve the domestic economy. The urgency of electronic land registration must be carried out to reach all levels of society, especially rural areas. Routine and continuous outreach is carried out to increase public knowledge in the land sector, including handling information and complaints.